Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1098/rspb.2015.2869
|View full text |Cite
|
Sign up to set email alerts
|

Multiple evolutionary origins of Australian soil-burrowing cockroaches driven by climate change in the Neogene

Abstract: Parallel evolution is the independent appearance of similar derived phenotypes from similar ancestral forms. It is of key importance in the debate over whether evolution is stochastic and unpredictable, or subject to constraints that limit available phenotypic options. Nevertheless, its occurrence has rarely been demonstrated above the species level. Climate change on the Australian landmass over the last approximately 20 Myr has provided conditions conducive to parallel evolution, as taxa at the edges of shri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(75 citation statements)
references
References 37 publications
(53 reference statements)
9
64
2
Order By: Relevance
“…In the case of the Australian Schedorhinotermes, the timing of the split between this lineage and the Oriental Schedorhinotermes is consistent with a crossing over Wallace's line, either through rafting, or aerial dispersal across the short distances that are thought to have existed between some pairs of islands respectively with an Oriental and Australian/Papua New Guinean origin. Similar scenarios have been proposed to explain the presence of geoscapheine and panesthiine burrowing cockroaches in Australia (Lo et al, 2016). However, in that case, Australian cockroach taxa were found to be nested within Asian lineages, whereas this pattern was not found for Australian and Asian Schedorhinotermes.…”
Section: Discussionsupporting
confidence: 70%
“…In the case of the Australian Schedorhinotermes, the timing of the split between this lineage and the Oriental Schedorhinotermes is consistent with a crossing over Wallace's line, either through rafting, or aerial dispersal across the short distances that are thought to have existed between some pairs of islands respectively with an Oriental and Australian/Papua New Guinean origin. Similar scenarios have been proposed to explain the presence of geoscapheine and panesthiine burrowing cockroaches in Australia (Lo et al, 2016). However, in that case, Australian cockroach taxa were found to be nested within Asian lineages, whereas this pattern was not found for Australian and Asian Schedorhinotermes.…”
Section: Discussionsupporting
confidence: 70%
“…Divergence dates ranged from 0 to 25 mya (median age 2.4 mya). Eight taxa (26%) exhibited divergence‐date estimates pre‐dating the geological formation of Lord Howe Island, including plants (e.g., Thomas, Bruhl, Ford, & Weston, ; Wagstaff et al, ), invertebrates (e.g., Buckley et al, ; Lo et al, ) and a lizard (Chapple, Ritchie, & Daugherty, ) lineage. The univariate distribution plot of divergence times for Lord Howe Island taxa suggests an exponential increase of lineages with time, a strikingly similar pattern to that observed for NZ and Chatham Islands taxa (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…In each area, some individuals adapt to a novel niche created by the onset of aridity, and eventually become reproductively isolated from their parent species, which remains in the original niche. Although some studies have found evidence for an association between ancient aridification events and parallel evolution (Arab et al., ; Lo et al., ), the abiotic factors associated with these changes remain understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has since revealed that neither subfamily forms a natural group and that the taxa are in fact nested within one another, with soil burrowers independently emerging as sister species to the wood feeders up to nine times (Maekawa et al., ; Lo et al., ; Figure ). The wood‐feeding ancestors of modern geoscapheines are hypothesized to have independently evolved soil burrowing behaviour in response to the drying of the Australian continent during the Miocene period (Lo et al., ; Maekawa et al., ). As the availability of rotting logs decreased with the amount of rainforest cover, panesthiines that were previously adapted for burrowing into wood would have moved underground into soil in an attempt to seek out more humid conditions.…”
Section: Introductionmentioning
confidence: 99%